Pengaruh Lama Perendaman Biji Nangka Dalam Natrium Metabisulfit Dan Cara Pengeringan Terhadap Kualitas Tepung Biji Nangka - SYARIFUDIN, ENGGAR; , Dra. Suparti, M. Si (2016)
Jackfruit seeds are the source of carbohydrate, protein and energy. Jackfruit seeds have pouch of high carbohydrate, so they have potential in making flour. This research has goal to know the influence of long submerging jackfruit seeds in natrium metabisulfit and the way in drying to the quality of jackfruit seeds flour. This research uses completing disordered plan, factorial pattern contains of 2 factors. The first is the long submerging jackfruit seeds in natrium metabisulfit 600 ppm (N) these are 3 hours (N1), 4 hours (N2), and 5 hours (N3). The second is the way in drying (P) which is use 70°C during 2,5 hours (P1) and sun rayduring 3-5 days (P2). The parameter used is the degree of carbohydrate and the quality of flour which are including the texture, the color, the aroma, and the capacity of receiving. The result of this research shows that the long factor in drying in natrium metabisulfit has influence on the degree of carbohydrate and not influence on the quality of flour which are including the texture, the color, the aroma, and the capacity of receiving. The way in drying has influence in the degree of carbohydrate, the color, the capacity of receiving and not influence in the texture and the aroma. The highest degree of carbohydrate can be found in long treating of drying jackfruit seeds in natrium metabisulfit during 3 hours with the oven 70°C in drying during 2,5 hours (N1P1).